2024
DOI: 10.31989/bchd.v7i5.1348
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive peptides as alternative treatment for Helicobacter pylori infection

Giselle Franca-Oliveira,
Blanca Hernández-Ledesma,
Adolfo Martinez-Rodriguez

Abstract: The infection and chronic inflammatory response generated by Helicobacter pylori is a global health concern. This pathogen is characterized as a major risk factor in the development of gastric cancer and other diseases. Conventional eradication therapies are based on antibiotic regimens and as a consequence there is an increase in antimicrobial resistance of the pathogen strains, besides other potential side effects for the host. Therefore, it is necessary to explore new alternatives. This review delves into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The results obtained indicated that LSE might exert a protective effect against oxidative stress in H. pylori infected cells that could be attributed to protein/peptides or other bioactive compounds contained in the soybean extract. The antioxidant effects of lunasin and other soybean peptides have been previously reported in different cell and animal models, but not in H. pylori-infected cells [40,41]. Furthermore, other compounds present in LSE and not determined in this work could contribute to the reduction of ROS production by the cells.…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 56%
“…The results obtained indicated that LSE might exert a protective effect against oxidative stress in H. pylori infected cells that could be attributed to protein/peptides or other bioactive compounds contained in the soybean extract. The antioxidant effects of lunasin and other soybean peptides have been previously reported in different cell and animal models, but not in H. pylori-infected cells [40,41]. Furthermore, other compounds present in LSE and not determined in this work could contribute to the reduction of ROS production by the cells.…”
Section: Antioxidant and Anti-inflammatory Activity Of Lsementioning
confidence: 56%